Plastic tunnels for off season vegetable cultivation - Yadav, Deepika; Rajwade, Yogesh; Verma, Nilendra (Indian Farming, 2021)
In open field it is not possible to cultivate summer vegetable during winter due to lowtemperature, cold waves and high frost levels, and winter season vegetable during monsoondue to high rainfall intensity which directly damage plants or interfere with flowering andpollination. However, these crop scan grow inside the protective structure like green house, lowtunnel, and walk in tunnel, so that proper atmosphere may be given to plants for theirmaximum growth and yield. Though, the greenhouses has registered substantial growth inthe recent years on productivity and quality improvement but still the low cost protectedstructures like walk-in and low tunnel needs to be promoted due to poor financial status of ourfarming community.